ANALISIS PENGARUH PENGGUNAAN ABU BATU APUNG SEBAGAI PENGGANTI FILLER UNTUK CAMPURAN ASPAL - Kumalawati, A.; Sir, Tri M. W.; Mastaram, Yovinianus (Jurnal Teknik Sipil, 2013)
East Nusa Tenggara province is a region abundant with pumice content. Pumice is a frothy lava composed of compacted glass pyroclastic with very mikrovesikular wall extrusive igneous volcanoes bubbling, very thin and translucent and that is a common product of volcanic eruption and the general shape of the zones of the upper silicate lava They uses of pumice, among others: metal , raw material, lightweight brick, paint, plaster material, ceramics, sand paper raw materials and much more, pumice stone contain silica so that it can be used as a subtitude filler in asphalt mixture. This research was conducted to determine the effect of using pumice stone ash as a substitute filler in asphalt mixture. It will be seen from the value of stability and flow by using Marshall. There are several steps in Marshall’s method need to be done include: testing gravity, aggregate gradation planning, aggregate composition plane, aggregate bulk density calculation, the maximum mixture specific test and the calculations of the parameter values in Marshall’s method. The results of these research are finding higher levels of filler in asphalt mixture, the higher value of the stability while the value of flow decreases with increasing value of filler content in the asphalt mixture. Based on test results, the value of the variation of filler that meets spesifications Marshall’s is 1% and 2%, as only two variations of these filler levels that meet all of parameter value Marshall.